The Domain-Matrix : Performing Lesbian at the End of Print Culture - Case, Sue-Ellen (Book collections on Project MUSE., 1996)
"The Domain-Matrix is about the passage from print culture to electronic screen culture and how this passage affects the reader or computer user. Sections are organized to emulate, in a printed book, the reader's experience of computer windows. Case traces the portrait of virtual identities within queer and lesbian critical practice and virtual technologies. The book poses several key questions: How do the competing orders of print and the screen situate the body? How do they treat notions of the "live"? Written to encourage a reading strategy somewhere between print and hypertext, the book is divided into sections which prompt the reader to link them in non-sequential orders."--Jacket.